Fabrication and characterization of Ag-BaF2/GaSb Schottky diode - Abdulsamee Fawzi Abdulaziz (Tikrit Journal of Pure Science)
The Ag-BaF2/GaSb Schottky diode measurement has been investigated by using voltage versus current (I-V) at different temperatures, voltage versus capacitance (C-V) and hotoelectric measurements on n-type GaSb carrier per cm-3, Current – voltage measurement were used to study the interface layer. Near ideal characteristics were observed for Ag-BaF2/GaSb contact with ideality factor values (1.21-1.451). The Schottky barrier height and donor concentration (Nd) have been obtained from C-V characteristics. Barrier height results from these methods were the same approximately with the results obtained from current – voltage measurement and were in the same range which suggests that the Fermi level is pinned in the lower half of the band gap. Photoelectric measurements were used for barrier height measurements by applying the fowler method. The surfaces of sample was analyses using scanning electron microscopy (SEM) and also the x-ray is used to investigate the reasons for the non-ideal behavior of Ga contacts and to study the surface of Ag-BaF2 layer on the air-cleaved n-GaSb surface.